Meeting report from the joint IARC-NCI international cancer seminar series: a focus on colorectal cancer - Gunter, Marc J.R.; Alhomoud, S.; Arnold, M.; Brenner, Hermann; Burn, J.; Casey, G.; Chan, A. T.; Cross, A. J.; Giovannucci, E.; Hoover, R.; Houlston, R.; Jenkins, M.; et al. (Annals of oncology, 2019)
Despite significant progress in our understanding of the etiology, biology and genetics of colorectal cancer, as well as important clinical advances, it remains the third most frequently diagnosed cancer worldwide and is the second leading cause of cancer death. Based on demographic projections, the global burden of colorectal cancer would be expected to rise by 72% from 1.8 million new cases in 2018 to over 3 million in 2040 with substantial increases anticipated in low- and middle-income countries. In this meeting report, we summarize the content of a joint workshop led by the National Cancer Institute and the International Agency for Research on Cancer, which was held to summarize the important achievements that have been made in our understanding of colorectal cancer etiology, genetics, early detection and treatment and to identify key research questions that remain to be addressed.
Gesehen am 20.05.2020